The Role of Butylidenephthalide in Targeting the Microenvironment Which Contributes to Liver Fibrosis Amelioration - Chuang, Hong-Meng; Su, Hong-Lin; Li, Chien; Lin, Shinn-Zong; Yen, Ssu-Yin; Huang, Mao-Hsuan; Ho, Li-Ing; Chiou, Tzyy-Wen; Harn, Horng-Jyh (Frontiers in Pharmacology, 2016)
The treatment of liver fibrosis has clinical limitations because of its multiple etiologies, such as epithelial–mesenchymal transition (EMT) promotion, cell regeneration and remodeling dysfunction, inflammatory cell activation, and scar tissue deposition. These factors might be considered as a new target for the fibrotic microenvironment, leading to increased fibrogenesis and liver fibrosis. Here, we investigate a small molecule named butylidenephthalide (BP) and its multiple effects on liver fibrosis treatment. Thioacetamide was used in vivo to induce chronic liver fibrosis. BP was administered orally in rats for a period of 2 weeks and 4 weeks, which resulted in a significantly reduced fibrosis score (p<0.05) and (p<0.001), respectively. The inflammatory reaction of macrophage infiltration were reduced in the administration of BP, which led to the decrease in the transaminase levels. Moreover, we also found liver functions recovering (due to the increased serum albumin and reduced prothrombin time) where liver cells regenerated, which can be seen in the increase of Ki-67 on Oval cell. In addition, the fibrotic scar was also reduced, along with the expression of matrix metalloprotease by hepatic stellate cell. Furthermore, regarding the mechanism/study of EMT reduced by BP, the knockdown of BMP-7, which could reduce α-SMA expression, was mediated by the regulation of TGF-β, which implies its major role on EMT. Finally, in the in vivo study, BP treatment of liver fibrosis was reduced by Bmp7 knockdown in zebrafish, suggesting that BP leads to the reduction of liver fibrosis, which also depends on BMP-7 induction. These results suggest that BP had multiple targets for treating liver fibrosis in the following ways: reduction of EMT, decreasing inflammatory reaction, and liver cell proliferation. This multiple targets approach provided a new mechanism to treat liver injury and fibrosis.